P136: Increasing access to computed tomography scanning in the emergency department and its effect on patient outcomes. (May 2019) - Watson, M.; Richard, C.; Fortino, N.; Lyon, T.; Ohle, R.
Abstract : Background : There is growing concern about emergency physicians overuse of computed tomography (CT). In an attempt to ensure appropriate ordering many hospitals implement strict protocols for ordering of CT scans in the emergency department (ED) that include approval of all scans by a board-certified radiologist, and a reduced access to CT overnight.Aim Statement: The aim of this study is to review the impact of RAD ED – direct access to CT ordering by ED physicians, 24hr CT technologist and third-party reporting on CT scans overnight. Our objectives were to assess the effect on; 1) ED length of stay, 2) number of CT scans ordered and 3) admission rates.Measures & Design : We conducted a prospective pilot before & after study at a single tertiary-care emergency department between February 1st, 2018 and July 31st, 2018. Inclusion criteria were adult patients presenting to the emergency department and undergoing CT for any of the following: face, neck, spine, upper and lower extremities, chest, abdomen and pelvis. Exclusion criteria were those undergoing CT head for stroke or trauma.Evaluation/Results: A total of 924 patients met our criteria, 352 before and 568 after implementation. Comparison of the patient populations demonstrate very similar characteristics in both groups; (49% male, average age 56 years, CTAS 2(40%) and 3(47%). Results demonstrate that an additional 216 scans were performed in post-implementation group. This equates to an increase of 61%. ED length of stay averaged 5.6 hours pre-implementation and 4.7 hours post-implementation. This corresponds to a significant reduction in length of stay of approximately 0.9 hours (p < 0.01). Collection is currently ongoing for factors that we will adjust for a multivariate analysis, including admission rates.Discussion/Impact: RAD ED led to a significant increase in CT ordering and decrease in ED length of stay. We believe that this project provides important information to clinicians and patients with regards to overall CT utilization, ED wait times, follow up visits for CT scanning and admission rates. It is also important for administrators to help decide if these new rules are leading to improved efficiency, and to help estimate their financial impact.